Special Operations and Design Thinking: Through the Looking Glass of Organizational Knowledge Production. Issue 1 (2nd January 2016) - Zweibelson, Ben
Abstract : The U.S. military over the past decade has developed various forms of "design thinking" for complex problem solving in military conflicts. U.S. Special Operations Command (USSOCOM) has recently developed two operational design and design practitioners courses in an effort to integrate design thinking across all levels of USSOCOM. While the conventional Army uses one form of design, the organizational composition, mission, and high level of tacit knowledge production requires special operations to pursue other design concepts, design education options, and organizational improvements. This article outlines how and why special operations needs a different organizing philosophy for design in context, where the unique qualities of special operation missions require designing differently than conventional approaches.